If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1.1p + 14 = 16 Reorder the terms: 14 + 1.1p = 16 Solving 14 + 1.1p = 16 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 1.1p = 16 + -14 Combine like terms: 14 + -14 = 0 0 + 1.1p = 16 + -14 1.1p = 16 + -14 Combine like terms: 16 + -14 = 2 1.1p = 2 Divide each side by '1.1'. p = 1.818181818 Simplifying p = 1.818181818
| 5(3x-9)-6=5(x-3)+24 | | 2x^2+2x=264 | | -1-2w=-4 | | -3-(-5-2n)-6(1-5n)=9 | | 9+8m=6m-3 | | 2x-9+6x=-3(3+5x) | | [1+3c]-18=-8 | | 9+8m=-3 | | 4-3w=8.5 | | 3y-6x=-33 | | F[x]=2x+12 | | -10w=15 | | x(x+4)=6(2) | | 9=v+6-2 | | (5x)=-18 | | (2x+20)=(3x-10) | | 3(2x+1)-5x=2(x+1)-3 | | (2x-20)=(3x-10) | | 15=12x^2+24x | | 4d+8-2d=6d-10 | | -12x+2y=x+2 | | 7xy-4xy+2xy+6xy+3xy-7xy= | | 14x-(3x-7)=40 | | f(n)=2*f(n-1) | | 3(3z+1)-8=40 | | -1440=-15(-15x-29) | | 8u-1=8 | | (6+k)+12=23 | | 3(2x-7)-4(x-1)= | | 2h+10=66 | | 2h+10=66 | | y-8+124=180 |